Joint connection of experiment and simulation for photocatalytic hydrogen evolution: strength, weakness, validation and complementarity. Issue 11 (25th February 2021) - Luo, Jun; Liu, Yani; Feng, Chengyang; Fan, Changzheng; Tang, Lin; Zeng, Guangming; Wang, Lingling; Wang, Jiajia; Tang, Xiang
Abstract : The rapid developments of experiments and simulations have jointly promoted the progress of photocatalytic hydrogen evolution. Abstract : The rapid developments of experiments and simulations have jointly promoted the progress of photocatalytic hydrogen evolution. With the deepening of exploration, comprehensive research containing both experiment and simulation has become a mainstream trend. However, the complex relationships between experiment and simulation have not attracted enough attention, compared to the emphatically summarized advances. In this review, we begin with the brief introduction of experimental and simulation methods. Subsequently, the studies of interrelated experiments and simulations are elaborated to generalize their relationships. Moreover, we summarize the connections and differences between specific experimental means and simulation approaches, and critically analyze their respective merits and limitations. Finally, the prospects of how to integrate experiments and simulations more effectively and their common development in future photocatalytic hydrogen evolution are presented.